Canonical Wnt signaling is not required for Tgfb3 expression in the basal medial edge epithelium during palatogenesis - Saroya, Ghazi-Abdullah; Siismets, Erica; Hu, Max; Panaretos, Christopher; Rice, Adam; Reynolds, Kurt; Zhou, Chengji J.; Kaartinen, Vesa (Frontiers in Physiology, 2023)
The secondary palate forms from two lateral primordia called the palatal shelves which form a contact in the midline, become adherent at the fusing interface (medial edge epithelia, MEE) and subsequently fuse. The gene encoding transforming growth factor-ß3 (Tgfb3) is strongly and specifically expressed in MEE cells. Our previous study suggested that Tgfb3 expression is controlled via upstream cis-regulatory elements in and around the neighboring Ift43 gene. Another study suggested that the canonical Wnt signaling via ß-Catenin is responsible for the MEE-specific Tgfb3 gene expression, since deletion of the Ctnnb1 gene by a commonly used Keratin 14-Cre (K14Cre) mouse line almost completely abolished Tgfb3 expression in the MEE resulting in cleft palate. Here, we wanted to analyze whether Tcf/Lef consensus binding sites located in the previously identified regions of the Ift43 gene are responsible for the spatiotemporal control of Tgfb3 expression during palatogenesis. We show that contrary to the previous report, deletion of the Ctnnb1 gene in basal MEE cells by the K14Cre driver (the same K14Cre mouse line was used as in the previous study referenced above) does not affect the MEE-specific Tgfb3 expression or TGFß3-dependent palatal epithelial fusion. All mutant embryos showed a lack of palatal rugae accompanied by other craniofacial defects, e.g., a narrow snout and a small upper lip, while only a small subset (<5%) of Ctnnb1 mutants displayed a cleft palate. Moreover, the K14Cre:Ctnnb1 embryos showed reduced levels and altered patterns of Shh expression. Our present data imply that epithelial ß-catenin may not be required for MEE-specific Tgfb3 expression or palatal epithelial fusion.